PENGARUH EMPLOYEE HAPPINESS DAN KNOWLEDGE MANAGEMENT TERHADAP KINERJA INOVASI PADA PT. ASTRA TOYOTA AUTO 2000 ASIA AFRIKA BANDUNG - Adri Firdaus; Anita Silvianita (Universitas Bina Taruna Gorontalo, 2023)
This research was conducted to determine the effect Employee Happiness and Knowledge Management on Innovation Performance at PT. Astra Toyota Auto 2000 Asia Africa Bandung. This research uses quantitative methods with descriptive and causal research types. Sampling was done by non-probability sampling method or saturated sampling technique, with a total of 54 respondents. The data analysis technique used is descriptive analysis and Partial Least Square-Structural Equation Model (PLS-SEM) with the SmartPLS 4.0 analysis tool, The results of this study indicate that there is a positive and significant relationship between Employee Happiness and Innovation Performance, Employee Happiness and Knowledge Management, Knowledge Management and Innovation Performance as well as an indirect relationship between Employee Happiness and Innovation Performance through Knowledge Management. So that in improving innovation performance, paying attention to employee happiness and the application of knowledge management needs to be improved at PT. Astra Toyota Auto 2000 Asia Africa Bandung.